Computational Physics with Spreadsheet – III - Shetty, Mahesh; Mody, A K (SCHOOL SCIENCE, 2018)
In the first two articles of the series, we have discussed the use of EXCEL as a tool to understand graphs and variations of physical quantities with respect to each other based on equations. In this article, we go one step further to show how to understand phenomena that deal with variation with respect to time and space are understood using EXCEL. When students are taught the superposition of waves, they are merely shown the graphs of how these waves add in space (stationary waves) and in time (beats formation). These graphs are merely abstract representations unless they can draw or are shown how to draw. This calculation becomes very time-consuming unless we can use computers. Now this power is accessible to most students on their mobile, and MS-EXCEL is free for android users. In this article, we show how to study the formation of beats and stationary waves with the help of MS-EXCEL. How to use EXCEL is already discussed in the first article of the series